RING SPINNING MACHINES ON THE INFLUENCE OF THE SHAPE OF THE YARN CARRIERS ON THE DISTRIBUTION AND TENSION OF THE YARN (Web of Technology: Multidimensional Research Journal, 2024)
Thread guides of various shapes have been studied, and among them a thread guide is recommended, which is less affected by changes in the unevenness of the thread as a result of twist spreading.